Comparative Effect of Honey and Antibiotics against Multi Drug Resistant Bacteria Isolated from Surgical Site Infection - Syeda Rahmat Bibi; Zobia Afsheen; Hamza Iftikhar; Ranra Jalal; Saad Jan; Syed Majid Rasheed (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Patients undergoing surgery are predominantly exposed to surgical site infections (SSI) resulting in serious consequences. A cross-sectional study comprising 100 samples, was collected from various surgical sites of admitted and non-admitted patients in Lady Reading Hospital, Peshawar. 87 samples were tested positive for bacterial growth. After isolation and identification, the highest prevalence was recorded among isolates of Staphylococcus aureus 38 (43.6%) followed by Pseudomonas sp. 25 (28.7%), Streptococcus pyogenes 13 (14.9%) and E. coli 11 (12.6%). Antibiogram pattern was determined which showed high sensitivity of all bacterial isolates toward Clindamycin, Clarithromycin, and Piperacillin, followed by Erythromycin, Doxycycline, Co-amoxiclav, while maximum number of isolates showed resistance against Vancomycin, Ciprofloxacin, Amikacin. According to quantitative analysis, Ziziphus and Acacia honey inhibited E. coli at different Minimum Inhibitory Concentration (MIC). The results revealed that Ziziphus honey inhibited E.coli, at 100 µl concentration on the lowest MIC at 0.25 µl while Acacia honey inhibited E.coli at 75 µl concentration on lowest MIC at 0.5 µl. Ziziphus honey inhibited Pseudomonas sp. at 100 µl concentration on lowest MIC at 0.25 µl while Acacia honey inhibited Pseudomonas at 100 and 75 µl concentration on lowest MIC at 1 µl. Ziziphus honey also inhibited Staphylococcus aureus at 100 and 75 µl concentration on lowest MIC at 0.25 µl, while Acacia honey inhibited S. aureus at 100µl concentration on lowest MIC at 0.5 µl. This study concludes that Ziziphus honey was more effective in curing surgical wounds compared with Acacia honey. However, further Studies needed to be done for Ziziphus honey to utilize it as an efficient treatment approach.